Pengaruh Literasi Keuangan, Uang Saku dan Gaya Hidup terhadap Perilaku Menabung pada Siswa-Siswi Kelas 11 SMKS Thoriqul Ulum Pacet - Febrianti Kusuma Wardani, Astria; Hartono, Hartono; Verlandes, Yuliasnita (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The purpolse of this study is to determine the effect of financial literacylon saving behavior in thle SMKS Thoriqul Ulum Pacet. To ldetermine the effect of pocket moneyl on saving lbehavior in the SMKS Thoriqul Ulum Pacet. To determine lthe effect ofl lifestyle onl saving behavior in lthe SMKS Thoriqul Ulum Pacet. Tol determine lthe effect loffinancial literacy, pocket lmoneyl and lifestyle lon savingl behavior in the SMKS Thoriqul Ulum Pacet. The type of research used lis quantitative quantitative research methods are quantitative research methods which can lbe interpreted las researchl methods basedl lon positive philosophy, used to research cerltain populations or samples. This research uses independent variables and dependent variables. The testing stages consist of descriptive statistical analysis, data quality testing, classical assumption testing, multiple linear regression analysis. Financial Literacy simultaneously has a significant influence on the saving behavior of SMKS Thoriqul Ulum Pacet. Pocket Money, partially has a significant influence on the saving behavior of SMKS Thoriqul Ulum Pacet. Lifestyle partially does not lhave a significant effect onl the saving behavior of students at SMKS Thoriqul Ulum Pacet Financial Literacy, Pocket Money and lifestyle on saving behavior partially havela significant influence oln the savling behavior of students at SMKS Thoriqul Ulum Pacet.